Comparative tests of fuels for internal combustion engines - McKinnell, Fred B.; Johnson, Elmer (My University, 1908)
Introduction: Since the advent of the gasoline engine, the price of gasoline has constantly increased until now it is higher than that of kerosene. It is practically for this reason that these comparative tests were carried on, to decide whether an engine designed for gasoline could be run on kerosene fuel, and also to make a measurement of the relative maximum powers of the engine when using kerosene and the fuel for which it was originally designed.
Citation: McKinnell, Fred B. and Johnson, Elmer. Comparative tests of fuels for internal combustion engines. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Engines; Fuel; Engineering; Graduating theses; Senior theses; Theses